Synthesis and Characterization of Some Pyrimidinone Derivatives - IBRAHIM, M.N. (Asian Journal of Chemistry, 2010)
A series of pyrimidinone derivatives have been prepared through cyclocondensation reaction of asparagine with aromatic aldehyde derivatives to give 2-( substituted phenyl)-6-carboxy-1,2,3,5,6-pentahydro-4-(1H)-pyrimidinone.